Analysis of Supplier Selection Based on Circular Economy in Fashion Retail Company Using the Fuzzy AHP Method - Banuwati, Ninis; Hasibuan, Sawarni (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
Currently, the linear economic model applied in Indonesia still relies on a "take-make-dispose" pattern that is unsustainable. The circular economic approach emphasizes efforts to extend the life cycle of raw materials and product resources, minimize waste, and support the regeneration of natural systems. This research analyze the important role of suppliers in supporting circular economy success in the fashion retail compay. The objective of this study is to select and validate priority criteria and sub-criteria as a performance ranking framework for fashion retail industry suppliers using the Fuzzy Analytic Hierarchy Process (AHP) method. The results of the Fuzzy AHP analysis indicate that quality, delivery, cost, cooperation ability, and environmental performance criteria are the priority for ranking supplier performance in the fashion retail industry, with the highest weight assigned to the quality criteria. This is followed by subcriteria such as rejection rate and product price, which carry the highest subcriteria weights. This is because there is still a significant percentage of defective goods produced due to raw materials that are easily damaged or not in line with circular economic concepts. These recommendations can aid in more effective decision-making in selecting fashion retail suppliers, considering circular economic aspects and sustainable performance.